1989
DOI: 10.1051/parasite/1989646403
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii:Étude ultrastructurale des formations kystiques observées en culture de fibroblastes humains

Abstract: Toxoplasma gondii: Ultrastructure of cyst-like forms observed in human fibroblasts cell culture.SUMMARY. A strain of Toxoplasma gondii, non pathogenic to mice (Prugniaud strain) produced cyst-like stages when inoculated in human fibroblast culture. An ultrastructural study was performed in order to compare these cyst-like forms to brain cysts of the same strain and to intracellular clusters of tachyzoites observed in mice TG 180 sar coma cells.Electron microscopy confirmed the similarities between brain cysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…TEM studies have confirmed that the in vitro structures described here are comparable both to those described by previous authors [7][8][9] and cysts prepared from mouse brain. The differences in size between mouse brain and in vitro cysts may be attributable to the lack of tertiary structure in the monolayer and a limited nutrient supply; this may have a direct effect on the differentiation of the cysts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…TEM studies have confirmed that the in vitro structures described here are comparable both to those described by previous authors [7][8][9] and cysts prepared from mouse brain. The differences in size between mouse brain and in vitro cysts may be attributable to the lack of tertiary structure in the monolayer and a limited nutrient supply; this may have a direct effect on the differentiation of the cysts.…”
Section: Discussionsupporting
confidence: 90%
“…Lindsay et al [9] described some variation in cyst-forming activity using the isolate GT-1 when different host cells were adopted. Similarly, Jones et al [8] were able to produce long-lived 331 cyst cultures by use of a slowly dividing primary astrocyte culture. In the present study, we have achieved stabilised cyst cultures by removal of parasite-laden culture supernatant and refeeding the monolayer with fresh media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most strains of T. gondii will spontaneously develop tissue cysts in cell culture with no manipulation (22,109,111,113,156). However, the number of tissue cysts produced spontaneously is small and manipulation of the cell culture system is needed to increase this number (11,83,155,156,178).…”
Section: Methods Of Tissue Cyst Inductionmentioning
confidence: 99%
“…It has been reported that most T. gondii isolates can be maintained in various feeder-cell cultures, where most of them form cysts (Darde et al 1989;Jones et al 1986;Lindsay et al 1993;Smith and Lewis 1992). The majority of reports suggest that the production of cysts does not depend on the host-cell type, the culture medium, or the presence of immunological factors.…”
Section: Discussionmentioning
confidence: 99%